2012
DOI: 10.1128/aem.01386-12
|View full text |Cite
|
Sign up to set email alerts
|

Specific Fusion of β-1,4-Endoglucanase and β-1,4-Glucosidase Enhances Cellulolytic Activity and Helps in Channeling of Intermediates

Abstract: bIdentification and design of new cellulolytic enzymes with higher catalytic efficiency are a key factor in reducing the production cost of lignocellulosic bioalcohol. We report here identification of a novel ␤-glucosidase (Gluc1C) from Paenibacillus sp. strain MTCC 5639 and construction of bifunctional chimeric proteins based on Gluc1C and Endo5A, a ␤-1,4-endoglucanase isolated from MTCC 5639 earlier. The 448-amino-acid-long Gluc1C contained a GH superfamily 1 domain and hydrolyzed cellodextrin up to a five-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 34 publications
(47 reference statements)
1
36
0
1
Order By: Relevance
“…In previous studies we showed that Paenibacillus ICGEB2008 isolated from the gut of the cotton bollworm produced several biomass-degrading enzymes, including cellulases and hemicellulases1819. Therefore, we tested the expression levels in the gut microbes of major glycosyl hydrolase enzymes belonging to the categories of cellulase, hemicellulase, mannanase and glucanase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies we showed that Paenibacillus ICGEB2008 isolated from the gut of the cotton bollworm produced several biomass-degrading enzymes, including cellulases and hemicellulases1819. Therefore, we tested the expression levels in the gut microbes of major glycosyl hydrolase enzymes belonging to the categories of cellulase, hemicellulase, mannanase and glucanase.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolytic enzymes have been reported in both the extracellular and cell-bound fractions18192021. More often, the enzymes hydrolysing amorphous polysaccharides are secreted, while those hydrolysing crystalline substrates are found in the membrane-bound fraction of the bacteria1820.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to BglB, the BglB-Y301H mutant had reduced T m (40.5°C versus 47°C) (Fig. 5B and C) (36,37) and optimal temperature (35°C versus 45°C) (Fig. 4B).…”
Section: Similar Water Molecule Chains Have Been Observed In Bglb Andmentioning
confidence: 99%
“…There have been various attempts to produce multienzyme assemblies in vitro, including by gene fusion, protein or DNA scaffold construction, and chemical modification [3]. Although the simplest way is by enzyme fusion, this often results in loss of enzymatic activity or formation of inclusion bodies [4], while chemical modification can also impair enzymatic activity [5]. Moreover, the high cost of generating DNA scaffolds makes this approach infeasible on a large scale [6,7].…”
Section: Introductionmentioning
confidence: 99%